Epoxy and silicyl phosphorylcholine copolymer as well as continuous preparation method and application thereof
By preparing epoxy and silyl phosphocholine copolymers in microfluidic pipelines, the problems of cumbersome preparation methods and wide molecular weight distribution of MPC graft copolymers are solved, and a fast and simple copolymer preparation and efficient production process are achieved.
Patent Information
- Application Number
- CN202411855415.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-08
AI Technical Summary
The preparation method of graft copolymers of MPC is complicated, the molecular weight distribution of the copolymer is wide, and the proportion of monomer components is poorly controlled.
A continuous preparation method of epoxy and silyl phosphocholine copolymer is adopted to quickly prepare copolymers through microfluidic pipelines. The obtained copolymer has a narrow molecular weight distribution, simple preparation method, and is suitable for continuous production.
The rapid and simple preparation of copolymers is achieved, with narrow molecular weight distribution, improved production efficiency, and has good coating stability and anticoagulation effect.
Smart Images

Figure CN119775490A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copolymer preparation, and in particular to an epoxy and silylphosphorylcholine copolymer and a continuous preparation method and application thereof. Background Art
[0002] The structure of phosphorylcholine originates from biological cell membranes. The cell membrane surface is considered to be the best surface for the interaction of biological factors such as proteins and cells. It is soluble in a variety of organic solvents and water. Polymers containing phosphorylcholine groups are one of the potential materials for medical, pharmaceutical and bioengineering applications. 2-Methacryloyloxyethyl phosphorylcholine (MPC) is widely used in the preparation of phospholipid polymers because of its excellent free radical polymerization ability and easy copolymerization with other monomers. The polymer exhibits excellent anti-coagulation, high cell compatibility, resistance to protein adsorption and cell adhesion, and is widely used in the field of medical device coatings.
[0003] Glycidyl methacrylate (GMA) is a very useful monomer. Its chemical structure contains carbon-carbon double bonds and epoxy groups. It can undergo ring-opening reactions with various nucleophilic reagents, such as amine, hydroxyl and carboxyl groups. It is a good polymer reaction scaffold.
[0004] The free radical polymerization of MPC-GMA can be achieved by many methods. The current preparation methods mainly use atom transfer radical polymerization (ATRP) (Surasak Chantasirichot, Yuuki Inoue, Kazuhiko Ishihara. Photoinduced atom transfer radical polymerization in a polar solvent to synthesize a water-soluble poly(2-methacryloyloxyethyl phosphorylcholine) and its block-type copolymers[J]. Polymer, 2015, 61: 55-60) and emulsion stirring polymerization (Li-Ping Lv, Jian-Ping Xu. Disulfide-Crosslinked Biomimetic Micelles: Formation, Thiol Reactivity and Cytotoxicity Behavior[J]. Macromolecular Chemistry Physics, 2010, 211: 2292–2300) to prepare polymers with regular structures. However, the polymerization conditions are relatively harsh and it is difficult to industrialize them. Atom transfer radical polymerization is a controllable free radical polymerization method. The molecular weight distribution of the prepared polymer is narrow and controllable, but the metal ions in it are difficult to remove, which limits its application in the human body. Traditional emulsion stirring polymerization takes a long time and is intermittent. There are also certain safety risks. Due to the uneven heating of the solution, the molecular weight distribution of the obtained polymer is relatively broad and the controllability is poor. Summary of the invention
[0005] The present invention aims to solve the problems that the preparation method of the graft copolymer of MPC is complicated, the molecular weight distribution of the copolymer is wide, and the controllability of the proportion of monomer components is poor. A continuous preparation method of MPC-GMA-TSMA copolymer is provided. The copolymer is quickly prepared through a microfluidic channel. Not only does the molecular weight distribution of the obtained copolymer be narrow, but the preparation method is simple, continuous production can be realized, and production efficiency is greatly improved.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for continuously preparing an epoxy-silyl phosphorylcholine copolymer comprises the following steps:
[0008] Step 1, under the protection of inert gas, a vinyl monomer containing phosphorylcholine, a vinyl monomer containing epoxy, a vinyl monomer containing silane and a free radical initiator are dissolved together in a reaction bottle, the reaction solution is pumped into a high performance liquid chromatography pump through a pipeline, and then freely polymerized through a pipeline through a heating zone, and the generated copolymer solution flows into a receiving tank;
[0009] Step 2, adding a precipitant to the copolymer solution to obtain a precipitate, and drying, washing, and drying to obtain the epoxy and silylphosphorylcholine copolymer.
[0010] The present invention injects epoxy-containing vinyl monomers, silane-containing vinyl monomers, phosphorylcholine-containing vinyl monomers and initiators into a pipeline through a high-performance liquid chromatography pump, passes through a heating zone in the form of a fluid, and continuously and rapidly prepares phosphorylcholine polymers containing epoxy and silane through simple free radical polymerization. The traditional solution stirring preparation time is 20-24 hours, while the continuous preparation only requires 3-5 minutes. The monomer ratio in the polymer is easy to control, the preparation process is simple and efficient, safe, simple in equipment, low in cost, and convenient for industrial production.
[0011] Preferably, the vinyl monomer containing phosphorylcholine is one or more of 2-methacryloyloxyethyl phosphorylcholine (MPC) and carboxylic betaine methacrylate (CBMA);
[0012] Preferably, the epoxy-containing vinyl monomer is glycidyl methacrylate;
[0013] Preferably, the silane-containing vinyl monomer is 3-(methacryloyloxy)propyltrimethoxysilane (TSMA);
[0014] Preferably, the free radical initiator includes one or more of azobisisobutyronitrile (AIBN) and benzoyl peroxide (BPO).
[0015] In step 1, the molar ratio of the vinyl monomer containing phosphorylcholine, the vinyl monomer containing epoxy, and the vinyl monomer containing silane is 4-8:1-3:1-3; the mass of the free radical initiator is 0.1-3% of the total mass of all monomers.
[0016] The concentration of the total mass of all monomers in the reaction solution in step 1 is 0.1-0.3 g / ml; the solvent is selected from one or more of n-propanol, anhydrous ethanol, and tetrahydrofuran;
[0017] The temperature of the heating zone is 60-80°C, the time for the reaction liquid to pass through the heating zone is 2-10 minutes, and the pipeline and the high performance liquid chromatography pump are filled with 0.1-0.3MPa of inert gas.
[0018] Preferably, the pipe is made of polytetrafluoroethylene and has an inner diameter of 16-54 mm.
[0019] Preferably, in step 2, the precipitating agent is one or more of diethyl ether and n-hexane; the volume of the precipitating agent is more than 15 times the volume of the copolymer solution.
[0020] The present invention also provides an epoxy and silyl phosphoryl choline copolymer prepared by the preparation method, characterized in that the epoxy and silyl phosphoryl choline copolymer has a PDI of less than 1.5 and a number average molecular weight of 12500-16000. The method of the present invention can effectively control the proportion of monomers in the reaction raw materials, improve the reaction effect of the raw materials, the proportion of blocks in the product is more consistent with the input amount of raw materials, and the molecular weight distribution of the copolymer is narrower.
[0021] The present invention also provides a method for preparing a bionic adhesion coating, comprising the steps of: dissolving the epoxy and silylphosphorylcholine copolymer obtained by the preparation method to form a polymer solution; immersing a metal substrate in the polymer solution, taking it out and drying it, and ultrasonically cleaning it to obtain the bionic adhesion coating.
[0022] Preferably, the metal substrate is a nickel-titanium metal sheet; the substrate is cleaned, dried and plasma treated before use;
[0023] The mass concentration of the copolymer in the polymer solution is 1-5 mg / ml, the dipping time is 30-90 seconds, the drying time and temperature are 20-30 minutes and 60-80° C. respectively; the ultrasonic cleaning is performed by ultrasonicating in ethanol or water for 20-30 minutes.
[0024] The present invention also provides application of the bionic adhesion coating prepared by the preparation method in preparing anti-coagulation coating materials.
[0025] The present invention dissolves a phosphorylcholine polymer with epoxy and silane on the side chain in a polar solvent, and dips a plasma-treated nickel-titanium metal sheet into the solution. The silane in the polymer cross-links and hydrolyzes with the hydroxyl groups on the metal sheet, and at the same time, the epoxy groups in the polymer react with the hydroxyl groups on the metal sheet to undergo a ring-opening reaction and are stably anchored on the surface of the substrate. After drying and ultrasonic cleaning, a dense and stable anti-coagulation coating material is prepared. The cell membrane-mimicking structure coating of the present invention has broad applications in the fields of in vivo implant materials, tissue engineering, drug controlled release, and enzyme fixation.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The copolymer is prepared from epoxy vinyl monomer, silane vinyl monomer and phosphorylcholine vinyl monomer by a microfluidic method, thereby realizing continuous production and greatly shortening the reaction time for preparing the copolymer. The process is simple, safe and controllable, and has a narrow molecular weight distribution, better coating stability and broad prospects for industrial production. The polymer is coated on a Ni-Ti stent and has good stability and anti-coagulation effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the device for preparing MPC-GMA-TSMA polymer in the examples.
[0029] Figure 2 Schematic diagram of the coating process of the polymer on the Ni-Ti metal sheet in the embodiment.
[0030] Figure 3 The MPC-GMA-TSMA, MPC-GMA and MPC-TSMA copolymers prepared in Example 1, Comparative Example 1 and Comparative Example 2 are 1 H-NMR detection diagram.
[0031] Figure 4 The fluorescence images of the copolymer coating Ni-Ti metal surface prepared in the examples and comparative examples after adsorption of rhodamine 6G.
[0032] Figure 5 This is a dynamic whole blood detection diagram before and after MPC-GMA-TSMA copolymer coating Ni-Ti metal surface. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.
[0034] The raw materials used in the following specific embodiments are all purchased from the market.
[0035] Example 1
[0036] Step 1, weigh 40g of MPC (manufactured by Nanjing Le Tianran), GMA (manufactured by Aladdin) and TSMA (manufactured by Aladdin) respectively and dissolve them in a reaction bottle with 200ml of n-propanol (Sinopharm Reagent) solution, with a molar ratio of 8:1:1, weigh 0.4g of AIBN (manufactured by Aladdin) and dissolve it in the above, accounting for 1wt% of the total mass of the three monomers.
[0037] Step 2, under the condition that the receiving tank and the pipeline are filled with 0.2MPa Ar pressure, the reaction solution is pumped into the high performance liquid chromatography pump and passed into a 20mm polytetrafluoroethylene pipe, and the flow rate of the solution is 2ml / min; the reaction solution flows through the 75°C polytetrafluoroethylene pipe heating area, and the reaction solution stays in the heating area for 4min. The generated MPC-GMA-TSMA polymer mixed solution flows into the receiving tank, and the receiving tank is simultaneously connected to an argon bottle to keep the pressure in the tank at about 0.2MPa.
[0038] Step 3, adding anhydrous ether to the copolymer solution as a precipitate, the volume ratio of the reaction solution to anhydrous ether being 1:20, filtering the precipitate and drying it in a vacuum drying oven at 30°C for 1 hour, redissolving it in anhydrous ethanol and precipitating it again with anhydrous ether, repeating this process 3 times, and finally drying it in a vacuum drying oven at room temperature for 12 hours to obtain the MPC-GMA-TSMA polymer product, with a reaction yield of 90%.
[0039] Step 4, preparing the MPC-GMA-TSMA polymer prepared in this example into a 3 mg / ml anhydrous ethanol solution for later use;
[0040] The Ni-Ti metal sheet was ultrasonically cleaned with acetone, deionized water and ethanol for 30 min in sequence, then dried and placed in a plasma machine for 20 min. 2 Flow rate 100ml / min, power 200W;
[0041] The plasma-treated Ni-Ti metal sheet was immersed in a 3 mg / ml polymer solution for 60 seconds, then taken out and dried in an oven at 60°C for 30 minutes to allow the epoxy and silane in the polymer to undergo ring-opening and hydrolysis reactions with the hydroxyl groups on the metal sheet, respectively, thereby anchoring the polymer to the surface of the substrate. The bionic adhesion coating was then constructed by ultrasonic cleaning in anhydrous ethanol for 30 minutes.
[0042] Example 2
[0043] Step 1, weigh 40g of MPC, GMA and TSMA respectively and dissolve them in a reaction bottle with 200ml of n-propanol solution, the molar ratio of MPC, GMA and TSMA is 8:1:1, weigh 0.4g of AIBN and dissolve it in the above solution, accounting for 1wt% of the total mass of the three monomers.
[0044] Step 2, under the condition that the receiving tank and the pipeline are filled with 0.2MPa Ar pressure, the reaction solution is pumped into the high performance liquid chromatography pump and passed into a 20mm polytetrafluoroethylene pipe, and the flow rate of the solution is 4ml / min; the reaction solution flows through the 75°C polytetrafluoroethylene pipe heating area, and the reaction solution stays in the heating area for 2min. The generated MPC-GMA-TSMA polymer mixed solution flows into the receiving tank, and the receiving tank is simultaneously connected to an argon bottle to keep the pressure in the tank at about 0.2MPa.
[0045] Step 3, adding anhydrous ether to the copolymer solution as a precipitate, the volume ratio of the reaction solution to anhydrous ether being 1:20, filtering the precipitate and drying it in a vacuum drying oven at 30°C for 1 hour, redissolving it in anhydrous ethanol and precipitating it again with anhydrous ether, repeating this process 3 times, and finally drying it in a vacuum drying oven at room temperature for 12 hours to obtain the MPC-GMA-TSMA polymer product, with a reaction yield of 75%.
[0046] Step 4, preparing the MPC-GMA-TSMA polymer prepared in this example into a 3 mg / ml anhydrous ethanol solution for later use;
[0047] The Ni-Ti metal sheet was ultrasonically cleaned with acetone, deionized water and ethanol for 30 min in sequence, then dried and placed in a plasma machine for 20 min. 2 Flow rate 100ml / min, power 200W;
[0048] The plasma-treated Ni-Ti metal sheet was immersed in a 3 mg / ml polymer solution for 60 seconds, then taken out and dried in an oven at 60°C for 30 minutes to allow the epoxy and silane in the polymer to undergo ring-opening and hydrolysis reactions with the hydroxyl groups on the metal sheet, respectively, thereby anchoring the polymer to the surface of the substrate. The bionic adhesion coating was then constructed by ultrasonic cleaning in anhydrous ethanol for 30 minutes.
[0049] Example 3
[0050] The schematic diagram of the polymer preparation device is shown in Figure 1, which specifically includes:
[0051] Step 1, weigh 40g of MPC, GMA and TSMA respectively and dissolve them in a reaction bottle with 200ml of n-propanol solution, the molar ratio of MPC, GMA and TSMA is 8:1:1, weigh 0.4g of AIBN and dissolve it in the above solution, accounting for 1wt% of the total mass of the three monomers.
[0052] Step 2, under the condition that the receiving tank and the pipeline are filled with 0.2MPa Ar pressure, the reaction solution is pumped into the high performance liquid chromatography pump and passed into a 20mm polytetrafluoroethylene pipe, and the flow rate of the solution is 1ml / min; the reaction solution flows through the 75°C polytetrafluoroethylene pipe heating area, and the reaction solution stays in the heating area for 8min. The generated MPC-GMA-TSMA polymer mixed solution flows into the receiving tank, and the receiving tank is simultaneously connected to an argon bottle to keep the pressure in the tank at about 0.2MPa.
[0053] Step 3, adding anhydrous ether to the copolymer solution as a precipitate, the volume ratio of the reaction solution to anhydrous ether being 1:20, filtering the precipitate and drying it in a vacuum drying oven at 30°C for 1 hour, redissolving it in anhydrous ethanol and precipitating it again with anhydrous ether, repeating this process 3 times, and finally drying it in a vacuum drying oven at room temperature for 12 hours to obtain the MPC-GMA-TSMA polymer product, with a reaction yield of 90%.
[0054] Step 4, such as Figure 2 As shown, the MPC-GMA-TSMA polymer prepared in this example is prepared into a 3 mg / ml anhydrous ethanol solution for later use;
[0055] The Ni-Ti metal sheet was ultrasonically cleaned with acetone, deionized water and ethanol for 30 min in sequence, then dried and placed in a plasma machine for 20 min. 2 Flow rate 100ml / min, power 200W;
[0056] The plasma-treated Ni-Ti metal sheet was immersed in a 3 mg / ml polymer solution for 60 seconds, then taken out and dried in an oven at 60°C for 30 minutes to allow the epoxy and silane in the polymer to undergo ring-opening and hydrolysis reactions with the hydroxyl groups on the metal sheet, respectively, thereby anchoring the polymer to the surface of the substrate. The bionic adhesion coating was then constructed by ultrasonic cleaning in anhydrous ethanol for 30 minutes.
[0057] Comparative Example 1
[0058] Step 1, weigh 40g of MPC, GMA and TSMA respectively and dissolve them in a reaction bottle with 200ml of n-propanol solution, the molar ratio of MPC, GMA and TSMA is 8:1:1, weigh 0.4g of AIBN and dissolve it in the above solution, accounting for 1wt% of the total mass of the three monomers.
[0059] Step 2, under the condition that the receiving tank and the pipeline are filled with 0.2MPa Ar pressure, the reaction solution is pumped into the high performance liquid chromatography pump and passed into a 20mm polytetrafluoroethylene pipe, and the flow rate of the solution is 2ml / min; the reaction solution flows through the 75°C polytetrafluoroethylene pipe heating area, and the reaction solution stays in the heating area for 4min. The generated MPC-GMA-TSMA polymer mixed solution flows into the receiving tank, and the receiving tank is simultaneously connected to an argon bottle to keep the pressure in the tank at about 0.2MPa.
[0060] Step 3, adding anhydrous ether to the copolymer solution as a precipitate, the volume ratio of the reaction solution to anhydrous ether being 1:20, filtering the precipitate and drying it in a vacuum drying oven at 30°C for 1 hour, redissolving it in anhydrous ethanol and precipitating it again with anhydrous ether, repeating this process 3 times, and finally drying it in a vacuum drying oven at room temperature for 12 hours to obtain the MPC-GMA-TSMA polymer product, with a reaction yield of 90%.
[0061] Step 4, preparing the MPC-GMA-TSMA polymer prepared in this example into a 3 mg / ml anhydrous ethanol solution for later use;
[0062] The Ni-Ti metal sheet was ultrasonically cleaned with acetone, deionized water and ethanol for 30 minutes in sequence and then blown dry; the Ni-Ti metal sheet that had not been treated with plasma was immersed in 3 mg / ml polymer solution for 60 seconds, taken out, and dried in an oven at 60°C for 30 minutes, so that the epoxy and silane in the polymer would undergo ring-opening and hydrolysis reactions with the hydroxyl groups on the metal sheet respectively, thereby anchoring the polymer to the surface of the substrate, and then ultrasonically cleaned in anhydrous ethanol for 30 minutes to construct a bionic adhesion coating.
[0063] Comparative Example 2
[0064] Step 1, weigh 40g of MPC and GMA respectively and dissolve them in a reaction bottle with 200ml of n-propanol solution, the molar ratio of MPC to GMA is 9:1, weigh 0.4g of AIBN and dissolve it in the above solution, accounting for 1wt% of the total mass of the three monomers.
[0065] Step 2, under the condition that the receiving tank and pipeline are filled with 0.2MPa Ar pressure, the reaction solution is pumped into the high performance liquid chromatography pump and passed into a 20mm polytetrafluoroethylene pipe, and the flow rate of the solution is 2ml / min; the reaction solution flows through the 75°C polytetrafluoroethylene pipe heating area, and the reaction solution stays in the heating area for 4min. The generated MPC-GMA polymer mixed solution flows into the receiving tank, and the receiving tank is simultaneously connected to an argon bottle to keep the pressure in the tank at about 0.2MPa.
[0066] Step 3, adding anhydrous ether to the copolymer solution as a precipitate, the volume ratio of the reaction solution to anhydrous ether being 1:20, filtering the precipitate and drying it in a vacuum drying oven at 30°C for 1 hour, redissolving it in anhydrous ethanol and precipitating it again with anhydrous ether, repeating this process 3 times, and finally drying it in a vacuum drying oven at room temperature for 12 hours to obtain an MPC-GMA polymer product, with a reaction yield of 91%.
[0067] Step 4, preparing the MPC-GMA polymer prepared in this example into a 3 mg / ml anhydrous ethanol solution for later use;
[0068] The Ni-Ti metal sheet was ultrasonically cleaned with acetone, deionized water and ethanol for 30 min in sequence, then dried and placed in a plasma machine for 20 min. 2 Flow rate 100ml / min, power 200W;
[0069] The plasma-treated Ni-Ti metal sheet was immersed in a 3 mg / ml polymer solution for 60 seconds, then taken out and dried in an oven at 60°C for 30 minutes to allow the epoxy and silane in the polymer to undergo ring-opening and hydrolysis reactions with the hydroxyl groups on the metal sheet, respectively, thereby anchoring the polymer to the surface of the substrate. The bionic adhesion coating was then constructed by ultrasonic cleaning in anhydrous ethanol for 30 minutes.
[0070] Comparative Example 3
[0071] Step 1, weigh 40g of MPC and TSMA respectively and dissolve them in a reaction bottle with 200ml of n-propanol solution at a molar ratio of 9:1, weigh 0.4g of AIBN and dissolve it in the above solution, accounting for 1wt% of the total mass of the three monomers.
[0072] Step 2, under the condition that the receiving tank and pipeline are filled with 0.2MPa Ar pressure, the reaction solution is pumped into the high performance liquid chromatography pump and passed into a 20mm polytetrafluoroethylene pipe, and the flow rate of the solution is 2ml / min; the reaction solution flows through the 75°C polytetrafluoroethylene pipe heating area, and the reaction solution stays in the heating area for 4min. The generated MPC-TSMA polymer mixed solution flows into the receiving tank, and the receiving tank is simultaneously connected to an argon gas bottle to keep the pressure in the tank at about 0.2MPa.
[0073] Step 3, adding anhydrous ether to the copolymer solution as a precipitate, the volume ratio of the reaction solution to anhydrous ether being 1:20, filtering the precipitate and drying it in a vacuum drying oven at 30°C for 1 hour, redissolving it in anhydrous ethanol and precipitating it again with anhydrous ether, repeating this process 3 times, and finally drying it in a vacuum drying oven at room temperature for 12 hours to obtain the MPC-TSMA polymer product, with a reaction yield of 85%.
[0074] Step 4, preparing the MPC-TSMA polymer prepared in this example into a 3 mg / ml anhydrous ethanol solution for later use;
[0075] The Ni-Ti metal sheet was ultrasonically cleaned with acetone, deionized water and ethanol for 30 min in sequence, then dried and placed in a plasma machine for 20 min. 2 Flow rate 100ml / min, power 200W;
[0076] The plasma-treated Ni-Ti metal sheet was immersed in a 3 mg / ml polymer solution for 60 seconds, then taken out and dried in an oven at 60°C for 30 minutes to allow the epoxy and silane in the polymer to undergo ring-opening and hydrolysis reactions with the hydroxyl groups on the metal sheet, respectively, thereby anchoring the polymer to the surface of the substrate. The bionic adhesion coating was then constructed by ultrasonic cleaning in anhydrous ethanol for 30 minutes.
[0077] Comparative Example 4
[0078] Step 1, weigh 40g of MPC, GMA and TSMA and dissolve them in a reaction bottle of 200ml n-propanol solution, with a molar ratio of 8:1:1, weigh 0.4g of AIBN and dissolve it in the above solution, accounting for 1wt% of the total mass of the three monomers. Put a suitable magnet in the reaction bottle, connect the reaction bottle to an argon bottle, replace the gas in the reaction bottle three times, fill it with 0.2MPa Ar, and place the reaction bottle in an oil bath at 75°C and react at 500rpm for 24h.
[0079] Step 2, the product after the reaction was precipitated with anhydrous ether, the volume ratio of the reaction solution to anhydrous ether was 1:20, and the product was placed in a vacuum drying oven at 30°C and dried for 1 hour. After being redissolved in anhydrous ethanol, the product was precipitated again with anhydrous ether. This process was repeated 3 times and finally dried in a vacuum drying oven for 12 hours to obtain the MPC-GMA-TSMA polymer product, with a reaction yield of 90%.
[0080] Step 3, preparing the MPC-GMA-TSMA polymer prepared in this example into a 3 mg / ml anhydrous ethanol solution for later use;
[0081] The Ni-Ti metal sheet was ultrasonically cleaned with acetone, deionized water and ethanol for 30 min in sequence, then dried and placed in a plasma machine for 20 min. 2 Flow rate 100ml / min, power 200W;
[0082] The plasma-treated Ni-Ti metal sheet was immersed in a 3 mg / ml polymer solution for 60 seconds, then taken out and dried in an oven at 60°C for 30 minutes to allow the epoxy and silane in the polymer to undergo ring-opening and hydrolysis reactions with the hydroxyl groups on the metal sheet, respectively, thereby anchoring the polymer to the surface of the substrate. The bionic adhesion coating was then constructed by ultrasonic cleaning in anhydrous ethanol for 30 minutes.
[0083] The reaction yields of the three polymers prepared in Example 1, Example 2 and Example 3 were 90%, 75% and 90% respectively. The main reason for the different reaction times of the fluid flowing through the heating zone in the examples is that the reaction yield can reach about 90% when the heating reaction time reaches 4 minutes or more, and the yield is only 75% when the heating reaction time is 2 minutes. The main reason is that the heating reaction time is not enough, resulting in incomplete reaction and more monomer residues. The polymer prepared by the solution stirring process in Comparative Example 4 has a long preparation reaction time and there are certain safety risks.
[0084] Characterization and performance
[0085] 1. Nuclear magnetic resonance detection
[0086] The polymer was dissolved in deuterated methanol and diluted to a desired concentration to detect the delayed percentage and kinetics of monomer conversion using nuclear magnetic resonance (1H NMR) spectroscopy (400 MHz NMR spectrometer; JEOL Co., Ltd., Tokyo, Japan). The content of each component unit of the copolymers such as MPC-GMA-TSMA, MPC-GMA and MPC-TSMA prepared in Example 1 and Comparative Example 1 and Comparative Example 2 can be calculated using the ratio of the integrated areas on the NMR spectra.
[0087] like Figure 3 As shown, the hydrogen at δ=3.75 (N-CH2-, MPC, 2H), δ=2.83, 2.68 (epoxy, GMA, 2H) comes from MPC and GMA respectively, and δ=0.75 (silane, TSMA, 2H). Therefore, the content of monomers in the polymer can be calculated by comparing the peak areas at various locations, as summarized in Table 1.
[0088] Table 1 Molar proportion of each block of polymers prepared in Examples and Comparative Examples by NMR measurement
[0089]
[0090]
[0091] According to the results of NMR measurement, the molar ratio of monomers in the polymer prepared by the free radical polymerization method with continuous flowability in the embodiment is very close to the reaction feed ratio, and the solution polymerization effect is better than that of Comparative Example 4.
[0092] 2. Gel Permeation Chromatography (GPC) Detection
[0093] Gel permeation chromatograph, pump is Waters 515, Water 2487 UV absorption detector, columns are Waters STYRAGEL HR3, HR4 and HR5 (300x7.8 mm), N, N-dimethylformamide is used as mobile phase, flow rate is 1 ml / min, monodisperse polystyrene is used as standard. GPC test results are shown in Table 2.
[0094] Table 2 GPC data of copolymers prepared in Examples and Comparative Examples
[0095] sample Number average molecular weight (Mn) Polydispersity Index (PDI) Example 1 15876 1.05 Example 2 12782 1.17 Example 3 15327 1.08 Comparative Example 1 15476 1.1 Comparative Example 2 58743 1.08 Comparative Example 3 67986 1.03 Comparative Example 4 16789 1.93
[0096] According to the GPC test results, the molecular weight distribution of the polymer prepared by the microchannel is narrow. For example, the molecular weight distribution of the polymer prepared by traditional solution stirring in Comparative Example 4 is wide, which may be caused by the uneven solution temperature during the reaction process. The microchannel reaction is heated evenly and the reaction speed is fast, which can effectively avoid this problem.
[0097] 3. Coating Rhodamine 6G staining experiment:
[0098] The Ni-Ti metal sheet samples after coating prepared in the embodiment and the comparative example were dyed with a 200 ppm (mass) rhodamine 6G aqueous solution. Rhodamine 6G can be stably adsorbed on the MPC surface. The sample was immersed in the rhodamine 6G aqueous solution for 30 seconds, then washed twice in distilled water, each time for 30 seconds, and the surface was observed under a fluorescence microscope.
[0099] Rhodamine 6G fluorescence staining Figure 4 As shown, there is almost no Rhodamine 6G fluorescent dye on the surface of the Ni-Ti metal sheet that has not been hydroxylated in Comparative Example 1, indicating that the close physical adsorption of the polymer and the Ni-Ti metal sheet will make the coating easy to fall off. The fluorescence of the hydroxylated Ni-Ti metal surface of the MPC-GMA and MPC-TSMA binary polymer coatings in Comparative Examples 2 and 3 can be clearly observed, but the density of the fluorescent coating is lacking.
[0100] In Example 4, the Ni-Ti metal sheet coated with the MPC-GMA-TSMA ternary polymer hydroxylated by the traditional solution stirring method can be observed to be widely anchored on the surface of the substrate, but the coating has cracks and some of it has fallen off, which may be due to the wide molecular weight causing the lack of stability of some polymers. In Examples 1-3, the Ni-Ti metal sheet coated with the MPC-GMA-TSMA ternary polymer hydroxylated by the microchannel can be observed to have a uniform, stable and dense coating, indicating that the coating effect of the ternary polymer is better, mainly because the dual interaction of silane and epoxy with the hydroxyl group on the surface of the substrate makes the coating more dense and stable.
[0101] 4. Dynamic whole blood test:
[0102] Blood was collected from New Zealand white rabbits and 4 wt % sodium citrate aqueous solution was added at a ratio of 10% to prevent coagulation. ND-100-65, ID 6.3mm, OD 9.5mm) was cut into 37cm lengths and connected with silicone cannulas. The resulting tube ring volume was 11.5mL. First, physiological saline was injected and rinsed in a rotating water bath for 10min, and then replaced with 5mL of re-calcified sodium citrate whole blood (5mL rabbit blood containing 10% 4wt% sodium citrate, 250μL 0.15M CaCl 2 The test material is added to the tube, and the silicone sleeve is connected and then rotated at 10 rpm. The current rotation time is 10-40 minutes. Finally, the thrombosis on the surface of each sample is evaluated.
[0103] Dynamic whole blood test results Figure 5 As shown, by comparing Example 1 with the uncoated Ni-Ti metal, it was found that after 12 minutes, a large amount of thrombus was produced on the uncoated Ni-Ti metal, while there was no thrombus on the surface of the coated Ni-Ti metal, indicating that the coated metal has good anti-coagulation properties.
Claims
1. A continuous preparation method of epoxy and silyl phosphorylcholine copolymer, characterized in that: Includes steps: Step 1, under the protection of inert gas, a vinyl monomer containing phosphorylcholine, a vinyl monomer containing epoxy, a vinyl monomer containing silane and a free radical initiator are dissolved together in a reaction bottle, the reaction solution is pumped into a high performance liquid chromatography pump through a pipeline, and then freely polymerized through a pipeline through a heating zone, and the generated copolymer solution flows into a receiving tank; Step 2, adding a precipitant to the copolymer solution to obtain a precipitate, and drying, washing, and drying to obtain the epoxy and silylphosphorylcholine copolymer.
2. The continuous preparation method of epoxy and silylphosphorylcholine copolymer according to claim 1, characterized in that: The vinyl monomer containing phosphorylcholine is one or more of 2-methacryloyloxyethyl phosphorylcholine, methacryloylethyl sulfobetaine, and carboxylic acid betaine methacrylate; The epoxy-containing vinyl monomer is glycidyl methacrylate; The silane-containing vinyl monomer is 3-(methacryloyloxy)propyltrimethoxysilane; The free radical initiator includes one or more of azobisisobutyronitrile and benzoyl peroxide.
3. The continuous preparation method of epoxy and silylphosphorylcholine copolymer according to claim 1, characterized in that: In step 1, the molar ratio of the vinyl monomer containing phosphorylcholine, the vinyl monomer containing epoxy, and the vinyl monomer containing silane is 4-8:1-3:1-3; the mass of the free radical initiator is 0.1-3% of the total mass of all monomers.
4. The continuous preparation method of epoxy and silylphosphorylcholine copolymer according to claim 1, characterized in that: The concentration of the total mass of all monomers in the reaction solution in step 1 is 0.1-0.3 g / ml; the solvent is selected from one or more of n-propanol, anhydrous ethanol, and tetrahydrofuran; The temperature of the heating zone is 60-80°C, the time for the reaction liquid to pass through the heating zone is 2-10 minutes, and the pipeline and the high performance liquid chromatography pump are filled with 0.1-0.3MPa of inert gas.
5. The continuous preparation method of epoxy and silylphosphorylcholine copolymer according to claim 1, characterized in that: The pipe is made of polytetrafluoroethylene and has an inner diameter of 16-54 mm.
6. The continuous preparation method of epoxy and silylphosphorylcholine copolymer according to claim 1, characterized in that: In step 2, the precipitating agent is one or more of diethyl ether and n-hexane; the volume of the precipitating agent is more than 15 times the volume of the copolymer solution.
7. The epoxy and silylphosphorylcholine copolymer prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The PDI of the epoxy and silyl phosphoryl choline copolymer is below 1.5, and the number average molecular weight is 12500-16000.
8. A method for preparing a bionic adhesion coating, characterized in that: The method comprises the following steps: dissolving the epoxy and silylphosphorylcholine copolymer prepared by the preparation method according to any one of claims 1 to 6 to form a polymer solution; immersing a metal substrate in the polymer solution, taking it out and drying it, and ultrasonically cleaning it to obtain the bionic adhesion coating.
9. The method for preparing the bionic adhesion coating according to claim 8, characterized in that: The metal substrate is a nickel-titanium metal sheet; the substrate is cleaned, dried and plasma treated before use; The mass concentration of the copolymer in the polymer solution is 1-5 mg / ml, the dipping time is 30-90 seconds, the drying time and temperature are 20-30 minutes and 60-80° C. respectively; the ultrasonic cleaning is performed by ultrasonicating in ethanol or water for 20-30 minutes.
10. Use of the bionic adhesion coating prepared according to the preparation method of claim 8 or 9 in the preparation of anti-coagulation coating materials.
Citation Information
Patent Citations
Method for continuously and electrically synthesizing indoline compounds by using micro-reaction device
CN115011977A
Continuous preparation method and device of polymer
CN117924595A
Continuous flow synthesis method of zirconocene olefin polymerization catalyst
CN117964666A
Protein adhesion inhibitor
US20170101497A1